The methodology of creating interactive atlas mountain resettlement of the North Caucasus» - Irina Vladimirovna Chernova (Наука. Инновации. Технологии, 2022)
The article discusses the need to create the Atlas of settlement in the republics of the North Caucasus, due to the return of interest in the problems of the mountain population in the North Caucasus, as well as large volumes of unstructured information accumulated in this area. Describe the methods and approaches of creating interactive Atlas, based on existing experience, application of advanced GIS technologies, and integration of GIS technologies and the Web. Reveals the structure and content of analytical materials, the structure of their presentation. Describes the stages of preparation of the Atlas software environment of ArcGis and converting layouts into a format suitable for interactive work with Web browsers, as well as the main functionality of using the interactive Atlas.